Nonmineralized triradial conulariids from the lowermost Cambrian Stage 2 of the Olenek Uplift, Siberian Platform. (July 2022) - Sarsembaev, Zhiger A.; Marusin, Vasiliy V.
Abstract: In the early Cambrian fossil record, triradial symmetry is typical for anabaritids and occurs among carinachitids. The former are an extinct group of minute benthic cnidarians covered with a calcareous tubular exoskeleton. The origin of the anabaritids is poorly understood, but previously reported triradial pyramid-shaped steinkerns and molds of the oldest conulariids, Vendoconularia, from the upper Ediacaran of the White Sea region suggested the anabaritids were closely related to conulariids. However, triradial symmetry could originate independently in different lineages in the late Ediacaran and early Cambrian. Herein we describe a new taxon, Ilankirus kessyusensis new genus new species, from the base of the Cambrian Stage 2 of the Olenek Uplift (Siberian Platform). These fossils occur as ornamented steinkerns in the shape of trilateral pyramids and lack any relics of a mineralized exoskeleton. Abundant plastic deformations and fractures of the casts suggest the organism was weakly if at all mineralized. The steinkerns are encrusted with a thin patina of iron-rich chlorite (chamosite) formed because of a multistage diagenetic replacement of authigenic glauconite (glauconite–berthierine–chamosite) under reducing conditions of oxygen-depauperate pore- and seawater. Both lacking two major autapomorphies of the crown-group conulariids (mineralized periderm and quadrate cross section of the oral region of the periderm), the late Ediacaran triradial Vendoconularia and Terreneuvian Ilankirus represent stem-group conulariids. UUID: http://zoobank.org/a2ce04fa-36a5-485a-806c-f13f4749fc7f